EVALUASI PERAN KOMITE SEKOLAH (STUDI KASUS DI SMAN 1 BANGKO PUSAKO) - Satria Satria; Hasnah Faizah AR; Zulkarnain Zulkarnain (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
The school committee is a body or a non-profit and non-political, in the formbased on consultation and democratic by education stakeholders at unit level of education as arepresentation of the various elements responsible for the improvement of the quality of theprocess and outcomes of education. The school committee was formed to facilitate and increasethe participation of the stakeholders of the school to participate in formulating, establish,implement, and monitor implementation of school policy and accountability that focuses onquality of service to learners are proportionate and open. This study aims to reveal the exactrole will be undertaken by a committee of SMAN 1 Bangko Pusako accordance withKepmendiknas No. 044 / U / 2002 which states that the school committee acts as a conduit ofconsideration (advisory agency), support (supporting agency), controller (controlling angency ),and mediator. This study used a qualitative approach with descriptive research instrument isself researchers themselves and informants, data collection techniques of documentation andinterviews. These results indicate that the committee SMAN 1 Bangko Pusako not fully carryout their roles and functions in accordance with Kepmendiknas No. 044 / U / 2002. This is dueto the school committee is not active and effective, the school committee does not know whatis the role and function of the school committee even school committee does not have AD /ART and lack of coordination and good communication with the school. Besides the pattern ofschool leadership which is not transparent and does not involve the committee in any programplanning and implementation and decision making result in the school committee can not playproperly and effectively.